Eksplorasi Material Semen untuk Pengembangan Produk Elemen Estetik - I Ketut Suarna (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
Cement is a unique material, initially as the base material with the mainfunction as an adhesive for other materials whose existence is always covered. Nowdays, the application of cement materials in interior elements appears to be more honest. Natural ash color and cement characteristics are interesting things to be exposed. The use of cement material has also grown not only limited to the elements that make up space (floors, walls and ceilings), but has stepped into space facilities (furniture) and aesthetic elements. Through a series of experiments with the "design by doing" method, experiments were carried out by giving chemical treatments such as foam agents, adding magnesium carbonate powder and adding magnesium oxide to the base materials (cement, cement + sand) to explore and discover various potentials, uniqueness, peculiarities and lighter feature as new ideas in aesthetic elements product development in interior design. The results obtained from a series of experiments showed differences in the cement concrete characteristics through its texture, shape, number and size of pores and difference in weight .